Technological and economic catch up in the biotechnology sectoral innovation system in South Africa - Moonsamy, Ghaneshree (University of the Witwatersrand, Johannesburg, 2024)
Based on the global drive to move towards knowledge-based economies, several countries have identified biotechnology as a sector of interest for economic development. South Africa too, has identified this sector as a means to stimulate economic growth, bridge the inequality gap and reduce unemployment. Despite significant efforts to date, the impact and performance of the biotechnology sector on the socio-economic status of South Africa has been uninspiring. This study aims to evaluate the existing biotech-based sectoral system of innovation and assess potential pathways that may be undertaken to achieve technological and eventual economic catch-up by the country. Windows of opportunity that may entail technological, demand and institutional/public policies were also evaluated. This study used a mixed method approach, which firstly assessed the performance of the South African biotech sectoral system of innovation (SSI) in comparison to five other countries of interest. Thereafter, semi-structured interviews were conducted with 20 participants involved in the biotech triple helix system of innovation. Key findings indicated that South Africa performed poorly in comparison to other countries evaluated, which included the USA, Germany, Mexico, India and Singapore. Regardless of having pockets of excellence and enabling mechanisms such as supporting policies and available infrastructure, organisational capabilities and a highly fragmented national system of innovation are major limitations of the sector. These findings present a key message in that further, significant efforts are required to build on existing capabilities such that the country is able to increase its global standing in terms of biotech-based innovation. As a developing, upper middle income county, South Africa is unfortunately way of the mark in terms of economic catch up, however pathways of catch-up, specifically technology, demand and policy windows of opportunity do exist and need to be harnessed.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in the field of Innovation Studiesto the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Sectoral Systems of Innovation; National Innovation System; Latecomer firms; Biotechnology; Catch up, Middle-income trap; Science, Technology; Innovation (STI); UCTD; SDG-9: Industry, innovation and infrastructure